Lender-specific mortgage supply shocks and macroeconomic performance in the United States - Franziska Bremus; Thomas Krause; Felix Noth (Halle Institute for Economic Research (IWH), 2021)
This paper provides evidence for the propagation of idiosyncratic mortgage supply shocks to the macroeconomy. Based on micro-level data from the Home Mortgage Disclosure Act for the 1990-2016 period, our results suggest that lender-specific mortgage supply shocks affect aggregate mortgage, house price, and employment dynamics at the regional level. The larger the idiosyncratic shocks to newly issued mortgages, the stronger are mortgage, house price, and employment growth. While shocks at the level of shadow banks significantly affect mortgage and house price dynamics, too, they do not matter much for employment.
urn:nbn:de:gbv:3:2-134318
Keywords: E44; G21; R20; 330; credit supply shocks; mortgage market concentration; real effects from housing markets